Evaluation of health outcomes associated with medication in southern Portugal using a novel approach for medication review: ReMeD study - Espirito Santo, Margarida de Fatima Neto (Cranfield University, 2017)
Currently, a large portion of the world's population uses medication on a regular basis and uses health services frequently, mainly due to the increase of longevity and the growing number of chronic diseases (CD). Consequently, a correct medication management is needed in order to improve the responsible use of medicines and health outcomes. Portugal shows a high prevalence of CD such as hypertension, obesity, dyslipidaemia and diabetes. Moreover, the Algarve region presents some shortcomings in accessibility to healthcare. Therefore, this research project arises with the main aim of establishing a methodology to analyse the outcomes of the process of medication use (MU) through medication review (MR) , in a clinical practice setting in Southern Portugal (AEDMADA clinic), applied in the ReMeD study. Patient´s data was collected individually and then systematically analysed considering the humanistic, economic and clinical outcomes. A questionnaire (SAHL-S&E) was previously adapted for the Portuguese language aimimg to identify subjects with low health literacy (HL), which was then used during the MR. The ReMeD study was conducted in 118 patients, mainly 65 years, hypertense, diabetic, dyslipidemic and presenting a very high cardiovascular risk. Humanistic outcomes showed 25.4% of patients having low medication knowledge, 43.2% with low HL and about 25% being non-adherent to medication. Economic outcomes revealed that most patients were polymedicated (73.8%) and monitored by 2-3 Physicians, and about 15% suffering hospitalization in the last year. Negative clinical outcomes (NCO) were identified in 99.2% of patients, and 74.6% presented risks of developing NCO. As a whole, the ReMeD methodology seems appropriate to identify situations from the process of MU, useful to outline new strategies aimed to improve patient's MU and the empowerment for disease management. Applying this novel approach enables the conduction of MR in a clinical setting, allowing to pinpoint modifiable situations, contributing to improve health outcomes.
Keywords: Clinical outcomes; medication; medication management; outcomes; pharmaceutical care